Photofragmentation dynamics and dissociation energies of MoO and CrO - Cooper, G; Gentleman, A; Iskra, A; Mackenzie, S (AIP Publishing, 2017)
Neutral metal-containing molecules and clusters present a particular challenge to velocity map imaging techniques. Common methods of choice for producing such species - such as laser ablation or magnetron sputtering - typically generate a wide variety of metal-containing species and, without the possibility of mass-selection, even determining the identity of the dissociating moiety can be challenging. In recent years, we have developed a velocity map imaging spectrometer equipped with a laser ablation source explicitly for studying neutral metal-containing species. Here, we report the results of velocity map imaging photofragmentation studies of MoO and CrO. In both cases, dissociation at the two- and three-photon level leads to fragmentation into a range of product channels, some of which can be confidently assigned to particular Mo* (Cr*) and O atom quantum states. Analysis of the kinetic energy release spectra as a function of photon energy allows precise determination of the ground state dissociation energies of MoO (=44 064 ± 133 cm−1) and CrO (=37 197 ± 78 cm−1), respectively.